Evaluation of the Effectiveness of Comprehensive Smoke-Free Legislation in Indoor Public Places in Shanghai, China - Wei, Yanxia (Int J Environ Res Public Health, 2019)
This study evaluated compliance with the comprehensive smoke-free law in public indoor places introduced in Shanghai in March 2017. Observations and PM2.5 monitoring over 30 min intervals in 8 types of the venue were conducted three times: within a month before implementation and 3- and 12-months post implementation. Observations of evidence of smoking decreased from 66.2% before legislation to 52.8% three months after (p = 0.002) and 49.7% one year after (p < 0.001). The density of lit cigarettes also reduced significantly after implementation (p < 0.001). When adjusting for outdoor, indoor PM2.5 levels were significantly lower after the legislation, but only by a small amount (three months later: −0.27, p = 0.08; one year later: −0.12; p = 0.03). Evidence of compliance was weakest in farmer’s markets and bars, and smoking in male toilets did not change significantly. The reduction in smoking was affected by the management performance of their obligations. The comprehensive smoke-free law led to modest reductions in smoking and PM2.5 levels as a result, but from levels suggesting quite high levels of pre-compliance. However, compliance was limited in some areas, suggesting more effort is required on management to gain better compliance in some places like farmer’s markets, bars, and toilets.